Unraveling the Mechanism of Structural Stability and Electrochemical Performance of N/F‐Modified Li2FeSiO4: A First‐Principles Study. Issue 2 (11th December 2022) - Guo, Xialei; Hou, Yuhua; Zheng, Shouhong; Chen, Xuan; Li, Wei; Tao, Xiaoma; Huang, Youlin
Abstract: The influence of N/F substitution and site‐exchange of Li and Fe ions on properties of Li2 FeSiO4 are investigated by first‐principles calculation, including the structural parameters, mechanical, electrochemical, and magnetic properties of Li2 FeSiO4 . The calculated results show that site‐exchange of Li and Fe ions occurs during the removal of lithium ions for Li2 FeSiO3.5 R0.5 (R = O, N, and F), and the cell volume changes greatly. It is found that substitution of O with F can decrease the cell volume change and improve the cyclic stability of Li2 FeSiO4 . Furthermore, the theoretical average deintercalation voltages can be effectively reduced by N and F doping. The densities of states and magnetic moment show that substitution of O with N and F can improve the conductivity of Li2 FeSiO4, and F doping is conducive to the extraction of more Li + from Li2 FeSiO4 system. Abstract : The significant role played by N and F ions doping in influencing the properties of Li2 FeSiO4 is explored. In addition, based on electronic structure and magnetic moment, the influence mechanism of doping on the cyclic stability and electrochemical properties is investigated in details. The above studies can provide theoretical guidance for experiment to design and prepare high‐properties silicate cathode materials.